Modelling and simulation of discrete manufacturing industry. (2018) - Neeraj, R.R.; Nithin, R. Pranav; Niranjhan, P.; Sumesh, A.; Thenarasu, M.
Abstract: This paper focuses on discrete event simulation of a manufacturing unit using ARENA software. The simulation was carried out with an objective to study the flow of aluminium brake brackets in the factory and find out the bottlenecks and also to calculate the productivity and workforce requirements in the unit. The process flow chart of the aluminium bracket was drawn and processing time of each process was calculated using ARENA input analyzer tool and then fed into the software and simulated. For optimization of the results the other tools available in arena like Process Analyzer (PAN) and Opt Quest were used. The bottlenecks were found and a better model was suggested in order to overcome them. In the new (suggested) model, the productivity was found to have increased by 6% and the workforce requirements decreased by 8.33% when compared with the existing (actual) factory model. The method followed in this paper can be used to design process as well as factory layouts for better efficiency of workforces, to achieve optimal productivity and better use of resources.